(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The European Union, ASEAN and Mercosur drive many aspects of international trade through their work to promote integration and eliminate trade barriers, and jointly build economic influence. This, article examines how these union tariffs affect the development of global trade through eradication, harmonious rules and increased market access. Using a qualitative functioning, the study analyzes the study of the case of major economic unions and their trade policies, with statistical data on business models and economic development. The results highlight that unions have greatly promoted intra-regional trade in global markets, although challenges such as internal inequalities and external competition. The discussion is about these unions’ course to deliver benefits to a specific area in the balance of power with global trade shifts. The International Economic Association, at last, is accountable for the hinged-trade window, even though the degree of their attractiveness is conditioned by adaptability and the level of cooperation they can manage. This is an article that gives a detailed description of their effects and lists areas where policymakers may find common ground to make decisions.